A STUDY OF INTEGRATION OF SUPPLY CHAIN AND REVERSE LOGISTICS IN NEW PRODUCT DESIGN & DEVELOPMENT: A CASE STUDY ON THE BEST PRACTICES IN THE AUTOMOTIVE SECTOR - Shaikh, Mohammad Ali Raza (2012)
A globalized business environment and the ever changing customer demand are forcing many companies to change from their traditional way of mass manufacturing to the mass customized way. Manufacturing circle presently is going through a complete change in practice due to many reasons ranging from customer oriented products, short product life cycle, laws and regulations, stakeholders requirements and competition. Hence, the companies are trying to develop sustainable supply chain. For this purpose companies are trying to incorporate the features of supply chain and reverse logistics in the early design and development stages. There have been many studies done focussing on the logicality of the reverse logistics and suggesting some models for the design of optimum reverse logistics system which also keeps the cost of operation to minimum. However, there have been limited number of studies that are done on the relation of new product design and development with supply chain and reverse logistics, with the new product design incorporating and improving features of serviceability, disassemblability, remanufacturability, reusability, recycalbility to hasten its recycle and treatment process and further reduce the costs. This paper highlights the factors that motivate the companies to go for environmental friendly practice. This is followed by, new product design, Models for new product design/development. After that the focus of the paper is completely on the automobile sector, the environmental practices followed by the automobile sector. For meeting the purpose, analyses of the company’s that follows green practices is done. The research compares the strategies these companies have taken in implementing new environmental policies. With the help of these analyses importance of new product design/ development in supply chain and reverse logistics activities is investigated. Also, further this research highlights the importance of green supply chain practice.